Mechanical Properties of Short Sisal Fibre Reinforced Phenol Formaldehyde Eco-Friendly Composites. Issue 1 (February 2017) - Maya, M.G.; George, Soney C.; Jose, Thomasukutty; Sreekala, M.S.; Thomas, Sabu
Natural fibres are a good reinforcing material. Among the various natural fibres, sisal fibre is of particular interest, since its composites have high impact strength besides having moderate tensile and flexural properties compared to other ligno-cellulosic fibres. Sisal fibre is a promising reinforcement for use in composites on account of its low cost, low density, high specific strength and modulus, no health hazards, easy availability in some countries and renewability. The present work focused on the recent developments in the field of sisal fibre reinforced phenol formaldehyde composites with reference to the properties of sisal fibre, processing techniques, and the physical and mechanical properties of the composites. The mechanical properties of the composites show much improvement by the addition of sisal fibre of optimum fibre length 40 mm and fibre loading 54 wt%. The better fibre matrix interaction is shown by sisal-PF containing 54 wt%. The comparison with other natural fibres shows that sisal fibre is a good reinforcing agent in PF matrix. Flexural strength and impact strength of the composites were examined and are increased with increasing the fibre content. Ageing studies of the composites showed a similar trend to that of un-aged samples. Interestingly, water absorption test results show that composite with 54 wt% fibre loading have good interaction with the matrix and contains less voids.